The Rise of Crime in Affordable Housing in Suburbs, Case of Iran - MARYAM GHASEMI (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Housing is one of the fundamental needs for human to respond their primary needs such as food, rest, cleaning and having family, in other words, everything that related to the needs of body and soul of a human. Nowadays by increasing the population in the world the suitable shelter becomes a real problem. In the point of economic also the prices of the houses increase too much so it is not affordable for low-income people to have shelter easily. After the revolution in Iran country, there is huge immigration from the rural part to metropolitan areas. Most of these peoples belong to a low-income family, new couples and labours. Governments try to solve this problem by creating some policies. The aim of this study is to analyze the crime in affordable houses located in suburbs area. This research will answer the important factor that causes crime in affordable housing in suburbans. The case study in this research is Mehr houses created for low-income people in Iran. This research analyzed the factors which may cause to raise the crime in that area based on the literature review and previous analysis by different theories in this field. Data is collected by literature review, news, books, papers. The result of this research confirms the possibility of Mehr affordable houses in suburbs transfer to the area that raises the crime.